2020
DOI: 10.3390/cli8110124
|View full text |Cite
|
Sign up to set email alerts
|

Soil Carbon Sequestration Potential of Climate-Smart Villages in East African Countries

Abstract: Climate-Smart Villages (CSVs) were established by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) in the East African countries of Kenya, Tanzania and Uganda to test and promote a portfolio of climate-smart agriculture (CSA) practices that have climate change mitigation potential. This study evaluated the soil carbon sequestration potential of these CSVs compared to the control land use that did not have CSA practices. At the one-meter depth, soil carbon stocks increased by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…SOC stock was increased by 100-267 Mg C ha −1 under land uses improved through CSA interventions compared with the control lands where no CSA interventions had been implemented. Previously, Ambaw et al [9] evaluated the contribution of CSA portfolio to soil carbon sequestration under different Eastern African countries and found out that CSA stored 50-95 Mg C ha −1 more SOC than the control, which is comparable with this study. The slightly higher carbon sequestration in this study than the one reported by Ambaw et al [9] could be explained by the following: (i) the farming systems are more intensive in this study than those identified by Ambaw et al [9], and (ii) the CSA interventions have been practiced for a decade in the present study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…SOC stock was increased by 100-267 Mg C ha −1 under land uses improved through CSA interventions compared with the control lands where no CSA interventions had been implemented. Previously, Ambaw et al [9] evaluated the contribution of CSA portfolio to soil carbon sequestration under different Eastern African countries and found out that CSA stored 50-95 Mg C ha −1 more SOC than the control, which is comparable with this study. The slightly higher carbon sequestration in this study than the one reported by Ambaw et al [9] could be explained by the following: (i) the farming systems are more intensive in this study than those identified by Ambaw et al [9], and (ii) the CSA interventions have been practiced for a decade in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Previously, Ambaw et al [9] evaluated the contribution of CSA portfolio to soil carbon sequestration under different Eastern African countries and found out that CSA stored 50-95 Mg C ha −1 more SOC than the control, which is comparable with this study. The slightly higher carbon sequestration in this study than the one reported by Ambaw et al [9] could be explained by the following: (i) the farming systems are more intensive in this study than those identified by Ambaw et al [9], and (ii) the CSA interventions have been practiced for a decade in the present study. Higher SOC stock under CSA is mainly attributed to carbon input through a combination of different practices, including crop residue incorporation [40], farmyard manure application [41], minimum tillage [42], and restricted-grazing which prevents residue removal [43].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A significantly high concentration of exchangeable Ca (18.21 ± 7.51 cmol/kg soil) for surface soils (0-15 cm) under agroforestry land use as compared to the control was probably due to decomposing litter that change the relative quantities of exchangeable base (Ca, Mg) and acid (Al, Fe) cations in soil [45]. Agroforestry through practices such as litter incorporation and manure application has been suggested to improve soil carbon sequestration [48].…”
Section: Soil Health Indicators Of Different Land Uses As Predicted B...mentioning
confidence: 99%